Club cell protein 16 in sera from trauma patients modulates neutrophil migration and functionality via CXCR1 and CXCR2 - Baolin Xu; Andrea Janicova; Jan Tilmann Vollrath; Philipp Störmann; Lukas Martin; Ingo Marzi; Sebastian Wutzler; Frank Hildebrand; Sabrina Ehnert; Borna Relja (BMC, 2019)
Abstract Background Club Cell protein (CC)16 correlates with lung injury and respiratory complications, which are in part triggered by polymorphonuclear leukocytes (PMNL) in severely traumatized patients (TP). CC16 exerts anti-inflammatory and immunosuppressive effects, however, its influence on PMNL functions after trauma is unknown. Here, we evaluated whether CC16 present in sera from TP could modify the biological functions of PMNL. Methods Sera from 16 severely injured TP without pneumonia (no P, n = 8) or with pneumonia (P, n = 8) were collected at admission to emergency department (ED) and 1 day prior pneumonia and pre-incubated with or without anti-CC16 antibody for CC16 neutralization. Samples from the equal post-injury days in the corresponding no P group were used. Neutrophils were isolated from healthy volunteers (HV, n = 5) and incubated with 20% of the serum medium from TP, respectively. In PMNL, CD62L, CD11b/CD18 and CD31 expression, migratory capacity, phagocytosis rate, oxidative burst and apoptosis were investigated. In isolated PMNL, CXCR1 and CXCR2 were neutralized before stimulation with CC16, and oxidative burst, phagocytosis and apoptosis were analyzed in neutrophils and their subsets. Results Serum from the P group enhanced significantly PMNL migration compared to no P group, while CC16-neutralization further increased the migratory rate of PMNL in both groups. CC16-neutralization increased significantly the expression of CD62L in the P group at ED. Oxidative burst was significantly increased in the P group vs. no P during the study period. CC16 seemed to have no influence on oxidative burst and phagocytosis in TP. However, in a more controlled study design, CC16 induced a significant increase of oxidative burst and a decrease of apoptosis of CD16+ granulocytes. These effects were markedly observed in mature CD16brightCD62Lbright and immune suppressive CD16brightCD62Ldim neutrophils. In mature subset, CXCR1 and CXCR2 neutralization diminished CC16-induced effects. Conclusions CC16 in sera from multiply traumatized patients, notably of those with pneumonia, has significant effects on PMNL. The results suggest an association of CC16 with CXCR1 and CXCR2. Our data suggest that CC16 reduces the migratory capacity of PMNL and thus modulates their function in patients with respiratory complications after trauma.